Complete Genome Sequence of Vibrio vulnificus MO6-24/O - Park, Jin Hwan (American Society for Microbiology, 2011)
Vibrio vulnificus is the causative agent of life-threatening septicemia and severe wound infections. Here, we announce the complete annotated genome sequence of V. vulnificus MO6-24/O, isolated from a patient with septicemia. When it is compared with previously known V. vulnificus genomes, the genome of this bacterium shows a unique genetic makeup, including phagelike elements, carbohydrate metabolism-related genes, and the superintegron.